Persuasion Processes in Consumer Intent to Read Online Product Reviews: A Study Based on the Elaboration Likelihood Model (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Studies have shown that many prospective consumers have the intention of reading online reviews of a product before purchasing that product online. How this intention arises, however, has not been extensively investigated. The study described here used the elaboration likelihood model (ELM) to examine the central and peripheral persuasion processes involved in shaping consumersâ€™ intent to read online product reviews. These two processes were operationalized by respectively using perceived review quality and perceived review consistency as constructs in a model of persuasion to read online reviews. The findings of the study suggest that consumersâ€™ intent to read online product reviews is shaped by their perception of such reviews as being either of high quality or as consistent with their prior knowledge about the product being reviewed. For an individual consumer, the persuasiveness of one of these processes over the other depends on the two respective moderators of consumer involvement and consumer expertise.Â